Sífilis congênita: incidência em recém-nascidos - ARAÚJO, Eliete da Cunha (Universidade Federal do Pará, 2013)
Since the detection of a significant increase in the number of cases by the mid 1980s that congenital syphilis is of growing epidemiological importance worldwide. Although measures of both prevention and control are available, congenital syphilis still continues to be a major public health problem. The main objective of this study was to determine the incidence of congenital syphilis among neonates born at the maternity of a large public hospital in Belem, Brazil- Fundação Santa Casa de Misericórdia do Pará - from May to September 1996. Interviews were made with 361 mothers and physical examination was routinely performed in their newborns. Serum samples from both mothers and neonates were tested by using three methods: one non treponema I antigen test (VDRL) and two treponemal antibody tests (FTA-Abs and ELISA IgM). The diagnosis of congenital syphilis was made in 9.1% of the neonates. The main findings of the present study could be summarized as follows: a)among the infected neonates 39,4% presented with clinical symptoms compatible with syphilis; b) 36.4% of Treponema pallidum infected mothers did not undergo prenatal medical follow up; c) 12.1% of these mothers reported being drug users and, for most of them, there were reports of previous stillbirth or spontaneous abortion; d) rates of bisexuality among fathers were higher in the group of syphilitic neonates if compared to those without the disease. Further and broader investigations should be carried out, in order to better understand the epidemiological features of syphilis in the Amazon region. As a consequence, effective prevention and control measures (and possibly erradication) would be implemented.